How to Upgrade Discipline Through Service Guidance Counseling In the Learning Process - Aisyah, Ratna; Reviola Putri; Restiana, Rita; Lestari, Septi (Yayasan Nurul Yakin Bunga Tanjung, 2023)
This research discusses how to improve discipline through counselling guidance services in the learning process at SMPN 1 Muaro Jambi from the point of view of the counselling guidance teachers and students. The type of research used is qualitative. The subject of this research is SMPN 1 Muaro Jambi, which consists of 6 classes, namely, VII A, VII B, VII C, VII D, VII E, VII F and three guidance and counselling teachers. These schools. The samples in this research were class VII F and 1 class VII counselling teacher using a purposive sampling technique. The data collection technique uses interviews, 15 interview questions for teachers and 25 interview questions for students, producing good interviews from teachers and students. These are sorted into the method of increasing discipline in the learning process. As for the research results, data was obtained that the technique for increasing specialisation in the learning process is through counselling guidance services, namely, dressing wholly and neatly (according to applicable school regulations), getting homework and checking homework, as well as maintaining the cleanliness of the school environment.